2020
DOI: 10.1080/13685538.2020.1806814
|View full text |Cite
|
Sign up to set email alerts
|

Levels of TNF-α, IL-6, IL-17, IL-37 cytokines in patients with active vitiligo

Abstract: Objectives: Vitiligo is an autoimmune disease, and its pathogenesis involves changes in cytokine levels in the affected patients. Tumor necrosis factor-alpha (TNF-a), interleukin (IL)-6, and IL-17 from pro-inflammatory cytokines, IL-37 in a recently detected anti-inflammatory activity. The aim of our study was to determine serum TNF-a, IL-6, IL-17, IL-37 levels in patients with vitiligo to understand their possible roles in the disease etiology and to compare the results with the healthy controls. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Autophagic cell death rather than cell death with autophagy is another condition. Many studies have shown that the IL-17 level is higher in the serum and lesions of vitiligo patients compared to healthy individuals, suggesting its possible role in the pathogenesis of vitiligo [ 70 ]. The elevated IL-17 in lesions might contribute to the more autophagic vacuoles in melanocytes, and the autophagic process might be involved in the death of melanocytes in vitiligo by the IL-17 mediated ROS autophagy-associated cell apoptosis.…”
Section: Forms Of Melanocyte Death Induced By Oxidative Stress In Vitiligomentioning
confidence: 99%
“…Autophagic cell death rather than cell death with autophagy is another condition. Many studies have shown that the IL-17 level is higher in the serum and lesions of vitiligo patients compared to healthy individuals, suggesting its possible role in the pathogenesis of vitiligo [ 70 ]. The elevated IL-17 in lesions might contribute to the more autophagic vacuoles in melanocytes, and the autophagic process might be involved in the death of melanocytes in vitiligo by the IL-17 mediated ROS autophagy-associated cell apoptosis.…”
Section: Forms Of Melanocyte Death Induced By Oxidative Stress In Vitiligomentioning
confidence: 99%
“…IL-6 is secreted by T lymphocytes and macrophages. Increased serum levels of IL-6 are reported in patients with vitiligo [ 52 ], in particular in those with new lesions [ 53 ]. Oxidative stress may influence IL-6 expression.…”
Section: Vitiligo Pathogenesis: Ab Origine Development From Gene To Cellular Dynamicsmentioning
confidence: 99%
“…IL-17 is a pro-inflammatory cytokine with a clear connection to numerous inflammatory diseases, such as psoriasis. Serum and tissue levels of IL-17 are higher in vitiligo patients than in controls [ 49 , 53 , 57 ] and a positive correlation was observed between IL-17 levels and the duration and body surface area (BSA) of the disease [ 52 , 57 ]. IL-17 cytokines are produced mainly by T helper 17 (Th17) cells, which are increased in the serum of patients with active vitiligo [ 58 ] and a positive correlation was also found between circulating Th17 cells and BSA, suggesting a role in progressive disease [ 59 ].…”
Section: Vitiligo Pathogenesis: Ab Origine Development From Gene To Cellular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of IL-17A level in skin and serum of patients with vitiligo have also been found [5,18,19]. On the other hand, IL-17 + cells were detected in lesional and perilesional skin [14,20,21] in addition to in ltration of these cells into the upper dermis in patients with vitiligo [14,20].Positive correlations between vitiligo and early age of onset, disease duration, affected body surface area [14,22,23], and disease progression have been found [5,14,16,24,25].…”
Section: Introductionmentioning
confidence: 99%